A Novel Nonsense Mutation of ABCA8 in a Han-Chinese Family With ASCVD Leads to the Reduction of HDL-c Levels - Wang, Chen-Yu; Chen, Ya-Qin; Jin, Jie-Yuan; Du, Ran; Fan, Liang-Liang; Xiang, Rong (Frontiers in Genetics, 2020)
Atherosclerosis is a condition where the arteries become narrowed and hardened due to a buildup of plaque around the artery wall. Recently years, the incidence rate of AS was increasing and tended to be younger, AS has become the culprit of heart attack, heart failure and stroke. Previous studies have revealed that dyslipidemia including hypercholesterolemia, hypertriglyceridemia and reduced high density lipoprotein (HDL-c) were the important basis of AS. Mutations of dyslipidemia related genes have been proved to play a crucial role in the development of AS and Coronary Heart Disease (CHD). In this study, a Han-Chinese family with AS and CHD was enrolled and the lipid testing discovered an obvious reduced levels of HDL-c in the affected members.We then performed whole exome sequencing to explore the candidate genes of the family. After data filtering, a novel heterozygous nonsense mutation (NM_007168: c.3460C>T; p.R1154X) of ABCA8 was identified and validated to be co-separated in the family members by Sanger sequencing. Previous studies have proved that deleterious heterozygous ABCA8 mutations may disrupt cholesterol efflux and reduce HDL-c levels in humans and mice. This study may be the second report related to ABCA8 mutations in patients with reduced levels of HDL-c. Our study not only contributed to the genetic counseling and prenatal genetic diagnosis of patients with AS caused by reduced HDL-c levels, but also provided a new sight among ABCA8, cholesterol efflux and HDL-c levels.